A 2D Dy-based metal–organic framework derived from benzothiadiazole: structure and photocatalytic properties. Issue 13 (7th March 2023) - Zhu, Jing; Hua, Lin; Zhang, Yumeng; Wu, Hongying; Zheng, Fuwei; Shen, Hongyan; Gong, Haiyan; Yang, Liu; Jiang, Aiyun
Abstract : A 2D Dy(iii ) metal–organic layer (MOL 1 ) was synthesized under solvothermal conditions. Abstract : A 2D Dy(iii ) metal–organic layer (MOL 1 ) was synthesized under solvothermal conditions. Structural analysis suggests that the Dy(iii ) ions in each one-dimensional (1D) arrangement are evenly arranged in the form of broken lines. The 1D chains are linked to one another via ligands to form a 2D layer that generates a 2D surface with elongated apertures. The photocatalytic activity study suggests that MOL 1 exhibits good catalytic activity in flavonoids by the formation of an O 2 ˙ − radical as an intermediate. This is the first reported method of synthesizing flavonoids using chalcones.